The Orang Asli customary land : issues andchallenges / Hamimah Hamzah - Hamzah, Hamimah (Universiti Teknologi MARA, Shah Alam, 2013)
This paper briefly explains the unique relationships of Orang Asli with the customary land. It further demonstrates the common views that there is a collision between the Orang Asli notion of land ownership and that of the state. In particular the discussion highlights the interpretation of customary tenure under section 4 (2) (a) of the National Land Code, 1965 and it significance with the Orang Asli customary land. The paper also discusses the application of the United Nation Declaration on the Rights of Indigenous Peoples (UNDRIP) to the new Orang Asli Land Policy and how it affected them.